Inflammatory bowel disease manifestations in spondyloarthritis: considerations for the clinician. (2nd November 2021) - Lubrano, Ennio; Luchetti, Michele Maria; Benfaremo, Devis; Mauro, Daniele; Ciccia, Francesco; Perrotta, Fabio Massimo
ABSTRACT: Introduction: Spondyloarthropathies (SpA) are a group of inflammatory arthritis that can involve the spine and/or peripheral joints. Extra-articular manifestations, such as inflammatory bowel disease (IBD), are frequently observed within the clinical manifestations of SpA and are part of the SpA classification criteria. Evidence of IBD is observed in about 6–7% of SpA patients, and a silent, microscopic gut inflammation, could be present in up to 50% of patients. From a pathogenetic point of view, dysregulated microbiome and migration of T lymphocytes and other cells from gut to the joint ('gut-joint' axis) has been recognized, in the context of a common genetic background. Areas covered: The aim of this paper is to narratively review the recent evidences on the epidemiology, classification, clinical findings, pathogenesis, diagnosis, and treatment of IBD in patients with SpA and to provide advices for both rheumatologist and gastroenterologist in the management of IBD in SpA. Expert opinion: IBD manifestations in SpA frequently increase the burden of the disease and represent a clinical challenge, especially for the diagnosis, assessment, and treatment of patients affected by those conditions. New treatment strategies targeting both articular and intestinal manifestations are now available and may lead to a better outcome.